IOT RELATIONSHIP WITH SUPPLY CHAIN, WORK EFFECTIVENESS, AND INDIVIDUAL BEHAVIOUR - Ding Chong; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2021)
IoT is developing in many sectors, especially in the industrial and household sectors. IoT is expected to be a new solution in daily activities, especially those closely related to objects or machines. The IoT concept itself is developing innovative technology into an object, with the aim of innovation that makes activities more effective and efficient. Examples of the application of IoT in the industrial and household sectors are 1) Automatic curtain covers, 2) automatic water faucets, 3) automatic folding umbrellas, and 4) and automatic parking scan sensors. This time, the research method is descriptive qualitative method, by obtaining data based on relevant previous research and developing according to the researcher's thinking. The results of this study are: 1) Supply Chain, related to the existence of IoT, where supply chain activities will be more effective and efficient, 2) Work Effectiveness, related to IoT, where every job will be easier to do with the help of existing technology in the form of IoT, 3) Individual Behaviour, related to IoT, where every job will be easier to do with the help of existing technology in the form of IoT.